PENGARUH BIAYA KUALITAS TERHADAP TINGKAT PROFITABILITAS PERUSAHAAN (STUDI KASUS PADA THE MAJESTY HOTEL AND APARTMENT, WAKATOBI) - Sun Kim, Min; Indar, Indar; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine the effect of quality costs on company profitability. The method used is a descriptive method with a case study approach. Descriptive method is a research method carried out by collecting, presenting, and analysing data based on existing facts in a company or a method that aims to describe the nature of something that is going on at the time the research is carried out that is going on at the time the research is carried out and examine the causes of a particular symptom. Data was obtained from a questionnaire using 30 respondents from each department. The data was analysed using simple regression analysis. Validity testing is done to determine whether the data measuring instrument is valid. Meanwhile, the reliability test is carried out to determine whether the measuring instrument used is relatively consistent and will produce the same data when used twice or more. The conclusion drawn by the author in this study based on simple regression analysis is that there is a significant difference between quality costs and profitability levels.